2020
DOI: 10.1186/s13037-019-0229-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and root causes of surgical site infections at an academic trauma and burn center in Ethiopia: a cross-sectional study

Abstract: Background: Despite modern surgical techniques and the use of antibiotic prophylaxis, surgical site infection remains a burden for the patient and health system. It is a major cause of morbidity, prolonged hospital stay, and increased health costs. Thus, the main aim of this study was to determine the prevalence and root causes of surgical site infection among patients undergoing major surgery at an academic trauma and burn center in Ethiopia. Methods: A hospital based cross-sectional study was conducted on 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
(19 reference statements)
6
23
4
1
Order By: Relevance
“…In our study, 14.7% SSIs were superficial, followed by deep (3%) infections, which is different from Mezemir et al, 39 study that reported 40.7% and 37.4% were deep and organ spaced infections, respectively. In addition, a higher percentage of surgical procedures were general (39.1%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, 14.7% SSIs were superficial, followed by deep (3%) infections, which is different from Mezemir et al, 39 study that reported 40.7% and 37.4% were deep and organ spaced infections, respectively. In addition, a higher percentage of surgical procedures were general (39.1%).…”
Section: Discussioncontrasting
confidence: 99%
“…Besides, contaminated and dirty wound classes were six and seven times more susceptible to SSIs than clean wound classes. This finding is in line with Weldu et al, 46 Mezemir et al, 39 and Misganaw et al 28 studies. These types of wound classes are suitable for the colonization and multiplication of different pathogens.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These were also identified by other studies to be independent predictors of SSI. 11,54,[58][59][60] Patients who received postoperative prophylaxis for greater than 24 h after surgery had 3.5 times higher risk of developing SSI than those whose postoperative prophylaxis discontinued within 24 h after surgery. This can be attributed to the fact that prolonged use of prophylactic antimicrobials is associated with the emergence of resistant bacterial strains and the excess use of antimicrobials can contribute to secondary infections, such as those caused by Clostridium difficile.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of SSI is related to the level of contamination of the wound as demonstrated in a recent surveillance of surgical infections in NHS hospitals in England, which showed that the SSI risk following gastrointestinal tract procedures (especially large bowel surgery) reached 9.0% in 2018/19 [9]. While SSIs could be prevented by identifying and mitigating the predisposing factors, SSIs still have a significant burden on both the patient and health system in Sub Saharan Africa countries, where resources are limited, and the wound infection rates are higher than developed countries [10,11]. Moreover, there is a knowledge gap regarding SSIs incidence, related factors and microorganism in Sudan.…”
Section: Introductionmentioning
confidence: 99%